Enforcement of Norms of Women's Representation in The Regional House of Representatives of Pekalongan Regency, Period 2019-2024 - Teti Hadiati; Eni Purwanti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This Paper analyzes about enforcement the norm of women's representation in the Regional House of Representatives of Pekalongan Regency for the period 2019-2024 and its implications for regional policies related to women's issues. Empirical juridical research uses a qualitative approach. Data collection techniques using interviews, questionnaire and the documents studies. Technical analysis using interactive models. The results showed that, enforcement norms of woman’s representation in the Regional House of Representatives of Pekalongan Regency for the period 2019-2024 not effective because there are several factors that influence it, among others: 1) the substance of the norms of representation of 30% women in the legislative institutions contained in the electoral law is inconsistent because if the registration of political parties participants does not the requirements of 30% of Women's representation, political parties are allowed to improve the proposed candidates. The norm will make political parties election participants in recruiting Women as an only formality with jargon